IMPROVEMENT ANALYSIS OF LEARNING VOCABULARY ASSISTED WITH FLASH CARDS - Srundi Akbar Zaenuri; Nur Alamsyah (IKIP Siliwangi, 2020)
Vocabulary is a very important part of learning English that must be mastered by students to communicate well. This research try to analyze (1) discussions that often occur in pronunciation of vocabulary for students using the flash cards method; (2) implementing learning to read vocabulary in speaking skills; (3) learning evaluation system for pronunciatio1n of vocabulary for students using the flash cards method; (4) Improving pronunciation skill words to students through the flashcard method. The method used in this research was classroom action research (CAR). The research method also aims to memorize quickly the vocabulary they receive is important vocabulary they want for the continuity of learning English using the flashcard method. The results showed that students' vocabulary understanding improved after they were taught using flash cards Keywords: Vocabulary,Flashcard, CAR